2021
DOI: 10.1103/physrevlett.126.044301
|View full text |Cite
|
Sign up to set email alerts
|

Lubricated Friction and the Hersey Number

Abstract: Most frictional contacts are lubricated in some way, but is has proven difficult to measure and predict lubrication layer thicknesses and assess how they influence friction at the same time. Here we study the problem of rigid-isoviscous lubrication between a plate and a sphere, both experimentally and theoretically. The liquid layer thickness is measured by a novel method using inductive sensing, while the friction is measured simultaneously. The measured values of the layer thickness and friction on the disk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…2004; Bruus 2008; Veltkamp et al. 2021; Veltkamp, Velikov & Bonn 2022). In this case, a hydrodynamically steady state is present and the friction is a result of the shearing of the fluid layer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2004; Bruus 2008; Veltkamp et al. 2021; Veltkamp, Velikov & Bonn 2022). In this case, a hydrodynamically steady state is present and the friction is a result of the shearing of the fluid layer.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work (Veltkamp et al. 2021, 2022) we have analysed this type of flow in detail. It is concluded that, for the relatively gentle flows probed in these studies, the viscosity of the liquids makes the dominant contribution to the generated lift.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Stribeck curve is widely used to investigate the inter-ply slip behavior of prepreg [14,15]. In this curve, a new variable the Hersey number is defined by viscosity, velocity and pressure [16,17]. In the hydrodynamic lubrication region of the Stribeck curve, the Hersey number is linearly related to the friction coefficient.…”
Section: Introductionmentioning
confidence: 99%